Efforts to Increase Students' Curiosity and Learning Achievement IPAS in Grade IV Natural Phenomena Material - Winandika, Gigih (Lembaga Riset Mutiara Akbar, 2024)
The problem of this research is the low level of students' curiosity and their learning achievement in classroom lessons, especially natural phenomena material in grade IV of elementary school. This study aims to improve one of the national character educations, namely students' curiosity and student learning achievement. This type of research is classroom action research consisting of 2 cycles. The objects in this study were all 31 students in grade IV of elementary school consisting of 9 male students and 22 female students. The instruments used in data collection used tests/evaluations and observation sheets for teacher activities and student activities. The indicators in this study were an increase in students' curiosity, which was marked by an increase in the average acquisition of students' curiosity from cycle I to the next cycle, and learning achievement was declared successful if ? 85% had reached the KKM, namely 70. The results of the study showed that efforts to increase students' curiosity and student learning achievement in natural phenomena material. This can be proven by the increase in the average curiosity of students from cycle I, which is 22.41, increasing in cycle II to 39.50. The average value of student learning achievement in cycle I is 69.95 and classical completeness is 67.74% and the average cycle II is 75 and classical completeness is 96.30%. Thus, the research is considered sufficient because it has achieved the desired indicators.